Solid state NMR assignments of a human λ-III immunoglobulin light chain amyloid fibril - Pradhan, Tejaswini; Annamalai, Karthikeyan; Sarkar, Riddhiman; Hegenbart, Ute; Schönland, Stefan; Fändrich, Marcus; Reif, Bernd (Biomolecular NMR assignments, 2021)
The aggregation of antibody light chains is linked to systemic light chain (AL) amyloidosis, a disease where amyloid deposits frequently affect the heart and the kidney. We here investigate fibrils from the λ-III FOR005 light chain (LC), which is derived from an AL-patient with severe cardiac involvement. In FOR005, five residues are mutated with respect to its closest germline gene segment IGLV3-19 and IGLJ3. All mutations are located close to the complementarity determining regions (CDRs). The sequence segments responsible for the fibril formation are not yet known. We use fibrils extracted from the heart of this particular amyloidosis patient as seeds to prepare fibrils for solid-state NMR. We show that the seeds induce the formation of a specific fibril structure from the biochemically produced protein. We have assigned the fibril core region of the FOR005-derived fibrils and characterized the secondary structure propensity of the observed amino acids. As the primary structure of the aggregated patient protein is different for every AL patient, it is important to study, analyze and report a greater number of light chain sequences associated with AL amyloidosis.
Online veröffentlicht: 18. September 2020
Gesehen am 22.11.2023